Experimental evidence of nitrogen control on pCO2 in phosphorus-enriched humic and clear coastal lagoon waters - Peixoto, Roberta B.; Marotta, Humberto; Enrich-Prast, Alex (Frontiers in Microbiology, 2013)
Natural and human-induced controls on carbon dioxide (CO2) in tropical waters may be very dynamic (over time and among or within ecosystems) considering the potential role of warmer temperatures intensifying metabolic responses and playing a direct role on the balance between photosynthesis and respiration. The high magnitude of biological processes at low latitudes following eutrophication by nitrogen (N) and phosphorus (P) inputs into inland waters may be a relevant component of the C cycle, showing controls on partial pressure of CO2 (pCO2) that are still poorly understood. Here we assessed the strength of N control on pCO2 in P-enriched humic and clear coastal lagoons waters, using four experimental treatments in microcosms: control (no additional nutrients) and three levels of N additions coupled to P enrichments. In humic coastal lagoon waters, a persistent CO2 supersaturation was reported in controls and all nutrient-enriched treatments, ranging from 24-fold to fourfold the atmospheric equilibrium value. However, both humic and clear coastal lagoon waters only showed significant decreases in pCO2 in relation to the controlled microcosms in the two treatments with higher N addition levels. Additionally, clear coastal lagoon water microcosms showed a shift from CO2 sources to CO2 sinks, in relation to the atmosphere. Only in the two more N-enriched treatments did pCO2 substantially decrease, from 650 µatm in controls and less N-enriched treatments to 10 µatm in more N-enriched microcosms. Humic substrates and N inputs can modulate pCO2 even in P-enriched coastal lagoon waters, thereby being important drivers on CO2 outgassing from inland waters.